Sistem Pendukung Keputusan Strategi Pemasaran UMKM menggunakan metode Complex Proportional Assessment (COPRAS) - Hera Fransiska; Siregar, Gunayanti Kemalasari (Jurnal Ilmiah Sistem Informasi (JISI), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are pivotal to Indonesia's economy but face significant challenges in devising effective marketing strategies. This research aims to develop a decision support system to assist MSMEs in determining optimal marketing strategies. The study employs the Complex Proportional Assessment (COPRAS) method, selected for its capacity to proportionally evaluate alternatives against a set of benefit and cost criteria. The system was developed by integrating five main criteria: promotional costs, market reach, sales levels, customer satisfaction, and media effectiveness. Five alternative strategies were evaluated. The social media digital marketing strategy achieved the highest ranking with a utility value of (98.76%). The customer loyalty program (90.57%) and marketplace marketing (83.38%) were the next best-performing alternatives.The proposed decision support system offers objective and measurable recommendations, which enhances the effectiveness of marketing decision-making and supports MSME competitiveness in the digital age. Keywords: Decision support system, COPRAS, Marketing strategy, MSME, Multi-criteria decision making